Theta burst stimulation over the right Broca's homologue induces improvement of naming in aphasic patients. - Kindler, J; Schumacher, R; Cazzoli, D; Gutbrod, K; Koenig, M; Nyffeler, T; Dierks, T; Müri, R (2012)
BACKGROUND AND PURPOSE: Improvements of language production in aphasic patients have been reported following repeated 1-Hz transcranial magnetic stimulation over the nondamaged right hemisphere. Most studies examined aphasic patients in the chronic phase. The effect of transcranial magnetic stimulation application in acute or subacute patients has not been systematically studied. We aimed to evaluate whether continuous theta burst stimulation, an inhibitory protocol with a shorter application time than the common 1-Hz protocol, is able to improve naming performance in aphasic patients in different poststroke phases. METHODS: Eighteen right-handed aphasic patients performed a picture naming task and a language independent alertness test before and after the application of theta burst stimulation over the intact right Broca's homologue localized by the 10-20 electroencephalogram system in a randomized, sham-controlled, crossover trial. RESULTS: We found that naming performance was significantly better, and naming latency was significantly shorter, after theta burst stimulation than after the sham intervention. Patients who responded best were in the subacute phase after stroke. CONCLUSIONS: This setting with the short theta burst stimulation application time and the simple stimulation localization procedure is suitable for clinical purposes.